Predicting outcomes of mesenteric ischemia postcardiac surgery: A systematic review. Issue 7 (30th April 2022) - Kayali, Fatima; Sarodaya, Varun; Shah, Hussain I.; Hayat, Muhammad Y.; Leung, Marco S. T.; Harky, Amer
Abstract: Objective: This systematic review aims to identify predictors of outcomes of mesenteric ischemia in patients following cardiac surgery. Methods: A comprehensive literature search was done on EMBASE, PubMed, Ovid MEDLINE, and SCOPUS using keywords relating to bowel ischemia and cardiac surgery. Database search results were screened by at least two authors and 32 articles were selected for inclusion in this review. Results: Data on 1907 patients were analyzed. The mean age was 70.0 ± 2.99 years and the prevalence of bowel ischemia was 1.74%. Advanced age was a significant risk factor. 63.16% of patients reported were men, and 58.4% of patients died in hospital. There was heterogeneity in the reported significance of the following preoperative risk factors: hypertension, smoking status, type 2 diabetes mellitus, end‐stage renal disease, preoperative left ventricular ejection fraction <35%. Cardiopulmonary bypass (CPB) time, preoperative/operative intra‐aortic balloon pump (IABP) support, and inotrope usage were significantly associated with the development of mesenteric ischemia; however, other intraoperative factors including the type of cardiac surgery and duration of aortic cross‐clamping had varying levels of reported significance. There were discrepancies in the reported significance of leukocytosis and metabolic acidosis (pH <7.3) as postoperative markers. Postoperative vasopressor use, prolonged ventilation time, and elevation in lactate, transaminases, creatinine, and intestinal fatty acid‐binding protein (IFABP) levels were found to be strongly associated with bowel ischemia. Conclusion: This systematic review found the strongest associations of mesenteric ischemia postcardiac surgery to be advanced age, CPB time, rise in lactate, transaminases, creatinine, and IFABP. IABP support, vasopressor, and inotrope use as well as prolonged ventilation were strongly linked too.